2019
DOI: 10.1002/brb3.1253
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical thickness related to single nucleotide polymorphisms in the major histocompatibility complex region in antipsychotic‐naive schizophrenia

Abstract: Instructions The aim of this study was to explore the relationships between changes in cortical thickness and single nucleotide polymorphisms (SNPs) in the major histocompatibility complex (MHC) region in a group of antipsychotic‐naive schizophrenia (AN‐SCZ) patients. Methods Twenty‐five AN‐SCZ patients and 51 healthy controls (HCs) participated in this study. General linear models were used to identify associations between the average cortical thicknesses of each brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…enlarged ventricles) was one of the frequently reported structural abnormalities in schizophrenic patients and animal models [ 30 , 31 ]. Tao et al reported that the rs2021722 was significantly associated with cortical thickness in antipsychotic-naïve schizophrenia patients, indicating that the immune system may play critical roles in the pathology of schizophrenia via the modulation of the development of cerebral cortical structures [ 32 ]. Together, although the specific mechanism of interaction between immune system and schizophrenia is not fully known, the present study confirmed the association between the rs2021722 in the HLA region and the risk of schizophrenia in Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…enlarged ventricles) was one of the frequently reported structural abnormalities in schizophrenic patients and animal models [ 30 , 31 ]. Tao et al reported that the rs2021722 was significantly associated with cortical thickness in antipsychotic-naïve schizophrenia patients, indicating that the immune system may play critical roles in the pathology of schizophrenia via the modulation of the development of cerebral cortical structures [ 32 ]. Together, although the specific mechanism of interaction between immune system and schizophrenia is not fully known, the present study confirmed the association between the rs2021722 in the HLA region and the risk of schizophrenia in Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%